Building Resilience in the European Union in Times of Polycrisis and Challenges in the Cognitive Domain - Panayotova, Monika (Research Papers, 2024)
This aim of this publication is to draw attention to the need to build resilience in the societies and Member States of the European Union in times of “polycrisis” and challenges in the cognitive domain. Following an analysis of global risks and hybrid threats, as well as the emergence of artificial intelligence in today’s communication and security environment, certain recommendations and conclusions are drawn to enable the EU to exploit its potential to be a “multidimensional power”, overcoming non-kinetic challenges to vulnerabilities in democratic societies, citizens’ minds and emotions. In this research, a range of political science analysis methods were employed. In addition, the “mind maps” technique of the British psychologist Tony Buzan was implemented by enabling the synthesis of ideas through visual representations. On the eve of the European elections in 2024, the publication draws key conclusions and recommendations for overcoming the challenges of desinformation, perception management and psychological manipulation, which undermine trust in democratic institutions and prevent decision-makers from countering them. These include: building resilience through education, media literacy, critical thinking, digital competencies, mental toughness; the ability to think not only fast but also slow; the application of exponential design to strategic thinking; multilateralism and close cooperation with NATO.